Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite. Issue 1 (February 2021) - Iqbal, Shahid; Ahmad, Naveed; Javed, Mohsin; Qamar, Muhammad Azam; Bahadur, Ali; Ali, Shahid; Ahmad, Zahoor; Irfan, Rana Muhammad; Liu, Guocong; Akbar, Muhammad Bilal; Qayyum, Muhammad Abdul
Abstract: A series of ternary-composite were synthesized by the integration of 7% silver-mixed ZnO NPs with different contents (3.5–75 wt%) of sulfur-doped graphitic carbon nitride (S-g-C3 N4 ). A unique ternary-composite formed between Ag/ZnO and S-g-C3 N4 generates a vast number of catalytic active sites for photocatalytic degradation. The as-synthesized 7% Ag/ZnO nanocomposite showed maximum methylene blue (MB) degradation rate among the series (0–9%) under visible light. The synergistic eﬀects of the Ag/ZnO/S-g-C3 N4 ternary-composite enhanced photocatalytic activity, and photo-corrosion resistance was demonstrated successfully. The photo-corrosion of ZnO NPs was inhibited by simultaneous mixing Ag and coupling with S-g-C3 N4, which was verified through cyclic photo-degradation with six consecutive dye degradation tests. Interestingly, the 25% Ag/ZnO/S-g-C3 N4 ternary-composite exhibited a significant increase in photodegradation of MB. Graphical Abstract: ga1 Highlights: A series of ternary composite Ag/ZnO nanocomposite with S-g-C3 N4 were synthesized having a high photocatalytic ability. 7% Ag/ZnO nanocomposite showed maximum dye degradation rate among the series. The photocatalytic activity of 25% Ag/ZnO/S-g-C3 N4 is significantly increased by the integration of Ag/ZnO with S-g-C3 N4 .